Antipsychotic prescribing patterns on admission to and at discharge from a tertiary care program for treatment-resistant psychosis. - Lik Hang N Lee (PLoS ONE, 2018)
Retrospective data were collected from 330 individuals who were treated at a tertiary care program for treatment-resistant psychosis between 1994 and 2010. The main objectives were to compare the use of antipsychotic monotherapy to polypharmacy and to characterize within-individual changes in treatment and symptomatology between admission and discharge. At admission, individuals who were prescribed only one antipsychotic were comparable to those who were prescribed at least two antipsychotics with regard to demographics and symptom severity. The use of psychotropic medications other than antipsychotics was also similar between the two groups. However, the magnitude of antipsychotic utilization was greater in individuals who were receiving antipsychotic polypharmacy. In addition, a greater proportion received excessive doses at admission. Similar findings were observed when the two antipsychotic prescribing practices were compared at discharge. Three important patterns were identified when investigating within-individual changes. First, fewer individuals were prescribed more than one antipsychotic at discharge. This was accompanied by a general decrease in the magnitude of antipsychotic utilization. Second, the number of individuals who were prescribed clozapine had increased by discharge. Most who were already prescribed clozapine at admission had their doses increased. Third, improvements in symptomatology were observed across all of the subscales included in the Positive and Negative Symptom Scale (PANSS); 57.9% of individuals experienced a relative reduction in total PANSS scores exceeding 20%. Based on these findings, it is possible to alleviate symptom severity while reducing antipsychotic utilization when patients are treated at a tertiary care program for treatment-resistant psychosis.